The adverse effects on employees of the unbridled exercise of certain management prerogatives - Almario Chan, Jan Franz Norbert Joselito (2019)
There are certain rights and prerogatives belonging to employers that are not found in the Labor Code or in any other laws but are well-recognized in jurisprudence. Their significance is highlighted by the fact that a constantly growing number of cases involving the issue of the validity of the exercise by employers of their management rights and prerogatives have reached the Supreme Court.

Not having any clear-cut legal anchor, cases in the multitudes keep piling up in courts because of the seemingly endless stream of complaints filed by workers involving the issue of validity of the exercise by management of such rights and prerogatives as hiring, work assignments, working methods, time, place and manner of work, supervision of workers, working regulations, promotion, demotion and transfer of employees, lay-off of workers, and the discipline, dismissal and recall of work, rules against marriage, post- employment bans or prohibitions such as the non-compete, confidentiality, non-disclosure, non-solicitation, non-recruitment and inventions assignment clauses.

This paper intends to closely examine such rights and prerogatives
to ascertain and establish their intrinsic merits, their limitations, their legality and rationality and most importantly, their effects on such constitutionally and legally guaranteed fundamental rights of workers to full employment, security of tenure and social justice.

More importantly, this paper shall attempt at introducing a completely new amendatory provision in the Labor Code on management rights and prerogatives in order to effectively obviate further legal complications in the never-ending dramatic and dynamic interplay between the employer and the employee in the workplace.
Keywords: Management rights; Labor laws; Employers; Employees